Collaboration process between local government and public institution in preventing HIV/AIDS diseases - Eko Supeno, Dio Wicaksono Putranto (Opción, 2020)
The study aimed to examine the collaboration process between the Local Government and Public Institution in preventing HIV/AIDS disease. This study used a descriptive qualitative method. This study used Collaborative Governance by focusing the literature about the collaboration process model. The result of the study showed that there is only related to Health Institution and Local Public Hospital which is conducted 3 levels of HIV/AIDS disease prevention. In conclusion, the collaboration process between Local Government and Public Institution in preventing HIV/AIDS is not running well yet.